Circulatory response to vasodilator therapy in congestive cardiomyopathy. - Rossen, R M (1976)
Vasodilator therapy has been shown to have beneficial effects in heart failure. In order to evaluate the haemodynamic actions of vasodilator administration in primary congestive cardiomyopathy, sodium nitroprusside was infused intravenously at a rate of 15 to 100 mug/min to 12 patients. Mean arterial pressure fell 15 per cent from 86+/-3-0 to 72+/-2-4 mmHg (11-40 +/- -4 to 9-6 +/- 0-3 kPa), and there was a small but significant decrease in mean heart rate from 96 +/- 4-8 to 90 +/- 4-4 beats/min. These changes were accompanied by a significant decrease in mean pulmonary artery pressure from 40 +/- 2-2 to 26 +/- 2-8 mmHg (5-3 +/- 0-3 kPa to 3-5 +/- 0-4 kPa), mean pulmonary capillary wedge pressure from 25 +/ -2-2 to 16 +/- 2-1 mmHg (3-3 +/- 0-3 to 2-1 +/- 0-3 kPa), and left ventricular end-diastolic pressure from 27 +/- 1-8 to 17 +/- 1-5 mmHg (3-6 +/- 0-3 to 2-3 +/- 0-2 kPa). Cardiac index increased by an average of 48 per cent from 2-1 to 3-1 l/min per m2, and left ventricular stroke work index increased from 18-4 +/- 1-6 to 21-3 +/- 1-9 g m/m2. These results show that pronounced left ventricular dysfunction in patients with congestive cardiomyopathy is improved during vasodilator therapy.